PENINGKATAN KEMAMPUAN MEMBACA TEKS LAPORAN HASIL OBSERVASI MELALUI MODEL RECIPROCAL TEACHING PADA SISWA KELAS X TKJ SMK BUDI BANGSA PINRANG - Muhammad Yusuf Yunus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
This is a classroom action research which aims to describe the planning, implementation, and improvement of Reading Skills on Observations Text Reports in class X TKJ SMK Budi Bangsa pinrang by applying reciprocal teaching model approach. Samples were 31 students of class X TKJ SMK Budi Bangsa Pinrang of academic year 2014-2015. The subject teachers are considered successful in improving learning and planning with good result. At the action stage, the students have better attitude hanged proved by observation sheet. At the evaluation stage, the results of reading tests on the aspects of content, text structure, vocabulary, sentences, and mechanics show that students have not reached the predetermined level of completeness on the first cycle. The second cycle, students, have already achieved mastery in learning ability of reading observation text reports. Studets’ mastery on the first cycle is 38,71% improve to 90,32%; where as, the students’ average score on cycle I is 72,87% improve to 81,23% on cycle II. Based on the results of the study, it is concluded that the reciprocal teaching model approach can increase the reading skills of observations text reports in class X TKJ SMK Budi Bangsa Pinrang after two cycles had been conducted.